2020
DOI: 10.1038/s41598-020-68743-3
|View full text |Cite
|
Sign up to set email alerts
|

Eye alignment changes caused by sustained GDNF treatment of an extraocular muscle in infant non-human primates

Abstract: The ability of sustained treatment of a single extraocular muscle with glial cell line-derived neurotrophic factor (GDNF) to produce a strabismus in infant non-human primates was tested. Six infant non-human primates received a pellet containing GDNF, releasing 2 µg/day for 90 days, on one medial rectus muscle. Eye alignment was assessed up to 6 months. Five of the six animals showed a slow decrease in eye misalignment from the significant exotropia present at birth, ending with approximately 10° of exotropia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“… 17 In a previous strabismus animal model, multiple slender nerve fibers were connected to a neuromuscular junction, and the number increased from 4.2% to 21.3% in neuromuscular junctions with more than one axon due to the effects of neurotrophic factors. 14 The findings on neurotrophic factors also indicated its involvement in trophic signaling alterations in the EOMs, 20 which can trigger a microcascade of plasticity at the muscle and motor neuron levels. 6 It has been demonstrated that continuous treatment with a neurotrophic factor has the potential to correct eye alignment in a sustained manner, which may override compensatory mechanisms in the ocular motor system.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 17 In a previous strabismus animal model, multiple slender nerve fibers were connected to a neuromuscular junction, and the number increased from 4.2% to 21.3% in neuromuscular junctions with more than one axon due to the effects of neurotrophic factors. 14 The findings on neurotrophic factors also indicated its involvement in trophic signaling alterations in the EOMs, 20 which can trigger a microcascade of plasticity at the muscle and motor neuron levels. 6 It has been demonstrated that continuous treatment with a neurotrophic factor has the potential to correct eye alignment in a sustained manner, which may override compensatory mechanisms in the ocular motor system.…”
Section: Discussionmentioning
confidence: 97%
“… 6 It has been demonstrated that continuous treatment with a neurotrophic factor has the potential to correct eye alignment in a sustained manner, which may override compensatory mechanisms in the ocular motor system. 14 , 18 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 These neurotrophic factors have varying effects on extraocular muscle contraction properties, force generation, and relaxation rates, as well as extraocular muscle cross-sectional areas. [14][15][16][17][18][19] Sustained local administration of IGFI on extraocular muscle partially reversed eye misalignment in a nonhuman primate model of strabismus. 20 It is possible that the abrupt changes in the visual world and as well as the direct changes to muscle tension resulting from strabismus surgery or toxin administration trigger compensatory mechanisms that drive the oculomotor system back to presurgical ocular misalignment.…”
mentioning
confidence: 99%